Hepatocellular carcinoma metastasis to the mandibular ramus: a case report - Liu, Hongwei (Int J Clin Exp Pathol, 2019)
Hepatocellular carcinoma (HCC) is one of the most commonly reported cancers worldwide. Although the extrahepatic metastasis of this carcinoma has been reported frequently, the mandible is a rare site for HCC metastasis. Here we have presented a rare case of mandibular metastatic HCC in a 37-year-old man presenting with painless swelling over his right parotid gland for the previous 3 months. This patient had a history of HCC caused by a hepatitis C viral infection. The tumor cells exhibited eosinophilic and rich cytoplasm, and they appeared to be trabecular (similar to hepatic cells), with sinusoids between the tumor cells. Moreover, the tumor cells were positive for Hep Par-1 and Glypican-3 in the cytoplasm. A 64-multidetector-row computed tomography scan was performed, and it showed pathological tracer uptake in the right mandible. Therefore, an excisional biopsy was performed, and with the support of an immunohistochemical analysis, an HCC mandibular metastasis diagnosis was made. The patient was treated with radiotherapy and chemotherapy. This patient was followed up in the oncology department for 1 year, and he was still alive at the time this report was written. This extremely rare case highlights the differential diagnosis difficulties that can be encountered, and the importance of diagnostic clues, such as the clinical history, histopathology, and immunohistochemistry, in the establishment of a definitive diagnosis. Clinicians should be aware of the possibility of encountering HCC metastasis in the mandible, and take this into consideration in order to prevent a misdiagnosis.